Functional role of polyphenol rich butanol fraction of Rivea ornata in experimentally induced myocardial infarction: Preservation of Cell viability and Free radical neutralization - Akkiraju Sudheer, Mallela Vijaya, Nayakanti Devanna (Journal of Applied Pharmaceutical Science, 2021)
The main motto of the current in vivo study was to understand the role of polyphenolic butanol fraction of Rivea ornata in rodent model of myocardial infarction (MI). Polyphenolic fraction separated from crude ethanol extract in to butanol fraction by solvent/solvent fractionation from nonpolar to polar. Male wistar rats (n = 30) were assigned as control, isoproterenol (ISO), carvedilol, butanol fraction (200, 400 mg/kg, p.o.) groups. At the end of pretreatment, ISO is injected in two days to all groups except control to cause MI. Observations like Electrocardiogram, infarction markers (Lactate dehydrogenase, Creatine kinase-MB, C-reactive protein), Sodium–potassium adenosine triphosphatase and Calcium adenosine triphosphatase, oxidative stress markers [Catalase (CAT), Superoxide dismutase (SOD), Reduced glutathione (GSH) & Malondialdehyde (MDA)], inflammation markers Tumour Necrosis Factor alpha (TNF-α), Interleukins (IL-6 & 10) and histopathological examinations were performed in all groups. ISO induced changes like ST segment elevation, elevation of serum infarction markers, reduced membrane bound adenosine triphosphatases, reduced levels of CAT, SOD, GSH & higher MDA content, higher inflammation markers (TNF-α and IL-6) myocardial damage were positively restored by butanol fraction especially at 400 mg/kg. Hence, cardioprotective effect was could be due to its antioxidant, cardiac membrane stabilization, anti-inflammatory action.
Keywords: Rivea ornata, butanol fraction, isoproterenol, ATPases, oxidative stress, inflammation markers.